2019
DOI: 10.3390/qubs3010006
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Mapping of Orientation and Strain Gradients in Metals by Synchrotron 3D X-ray Laue Microdiffraction

Abstract: Synchrotron 3D X-ray Laue microdiffraction, available at beamline 34-ID-E at Advanced Photon Source in Argonne National Laboratory, is a powerful tool for 3D non-destructive mapping of local orientations and strains at sub-micron scale in the bulk. With this technique, it is possible to study local residual stresses developed during manufacturing or while in service due to interactions between, for example, different phases and/or grains with different orientations in materials containing multiple or single ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Concerning residual stresses, which have not been mapped in the present work, they may as well be of high importance. Other works have reported very large residual stress even within recrystallizing grains [11,12]. It is thus suggested to include strain mapping in future studies of recrystallization, as residual strains are likely a missing link in identifying nucleation sites and understanding local migration phenomena.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning residual stresses, which have not been mapped in the present work, they may as well be of high importance. Other works have reported very large residual stress even within recrystallizing grains [11,12]. It is thus suggested to include strain mapping in future studies of recrystallization, as residual strains are likely a missing link in identifying nucleation sites and understanding local migration phenomena.…”
Section: Resultsmentioning
confidence: 99%
“…Recent developments of advanced synchrotron Xray techniques have enabled 3D non-destructive mapping of both crystallographic orientations and residual strains with very high angular resolution as well as good spatial and strain resolutions [5][6][7][8][9]. By such synchrotron measurements, it was revealed that a network of very low angle (<0.1°) dislocation boundaries and local residual strains as large as 1×10 -3 may exist within recrystallizing grains [10][11][12]. It is thus of interest to study interior misorientations and strains in recrystallizing grains in more detail using these advanced experimental methods, to understand effects hereof on 1249 (2022) 012050 IOP Publishing doi:10.1088/1757-899X/1249/1/012050 2 the nucleation and growth of recrystallizing grains, and to follow the evolution during the recrystallization anneal.…”
Section: Introductionmentioning
confidence: 99%
“…From the energy scans at the chosen sample position, the intensity distribution of the diffracted beam as a function of the diffraction vector was determined for each depth, and this distribution was fitted using a Gaussian function (see Figures S3 and S4 in the Supplementary Materials). The center of the Gaussian function was used to determine the spacing of the diffraction planes [17,20]. By comparing to the unstrained plane spacing (here taking the theoretical lattice constants a = 4.0495 Å for Al [21] and a = 2.9508 Å and c = 4.6855 Å for Ti [22]), the lattice strain along the plane normal was determined and termed ε ND , as the plane normal is very close to the ND of the tensile sample.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past two decades, significant effort has been devoted to the development of synchrotron techniques for characterizing 3D grain structure and local stresses, including 3D X‐ray Laue microdiffraction (3DμXRD) 30–32 and 3D X‐ray diffraction (3DXRD) 33,34 and its variants: high‐energy X‐ray diffraction microscopy, 35,36 diffraction contrast tomography, 37,38 dark field X‐ray microscopy, 39,40 and scanning 3DXRD 41 . Among these techniques, 3DμXRD is in particular suitable for mapping microstructure and strain/stress state in bulk samples, as it can provide a spatial resolution of submicrometer, angular resolution of 0.01°, and a strain resolution of 1 × 10 −4 32,42 …”
Section: Solid‐state Coolingmentioning
confidence: 99%